2016
DOI: 10.1097/pcc.0000000000000716
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Phenylephrine, Vasopressin, and Epinephrine in Children With Pulmonary Hypertension: A Pilot Study*

Abstract: This prospective pilot study of phenylephrine, arginine vasopressin, and epinephrine in pediatric patients with pulmonary hypertensive showed an increase in aortic pressure with all drugs although only vasopressin resulted in a consistent decrease in the ratio of pulmonary-to-systemic vascular resistance. Studies with more subjects are warranted to define optimal dosing strategies of these medications in an acute pulmonary hypertensive crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…However, the addition of vasopressin had no effect on this parameter in either group, during either normoxic or hypoxic ventilation. These data are in accord with recent studies of vasopressin in pulmonary hypertension that, while noting a vasopressin‐induced decrease in the pulmonary‐to‐systemic pressure ratio, ascribe this improvement to a rise in aortic pressure rather to pulmonary vasodilation . Vasopressin may be unique among pressors in having no pulmonary constrictor effect, but we concur that it has no apparent pulmonary vasodilator effect .…”
Section: Discussionsupporting
confidence: 91%
“…However, the addition of vasopressin had no effect on this parameter in either group, during either normoxic or hypoxic ventilation. These data are in accord with recent studies of vasopressin in pulmonary hypertension that, while noting a vasopressin‐induced decrease in the pulmonary‐to‐systemic pressure ratio, ascribe this improvement to a rise in aortic pressure rather to pulmonary vasodilation . Vasopressin may be unique among pressors in having no pulmonary constrictor effect, but we concur that it has no apparent pulmonary vasodilator effect .…”
Section: Discussionsupporting
confidence: 91%
“…Vasoactive agents such as milrinone, dobutamine, or low dose epinephrine, are chosen to improve inotropy while decreasing SVR. When dealing with systemic hypotension, particularly in the face of concomitantly increasing PVR, vasopressin may be an effective option for reversing these trends while maintaining MAP and perfusion [12].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adults undergoing cardiac surgery compared vasopressin to norepinephrine for treatment of vasoplegic shock and found that patients receiving vasopressin had lower mortality, shorter ICU stay, and lower incidence of renal injury . Phenylephrine, an alpha 1 agonist, has a similar vasoconstrictive effect on the systemic vasculature but, unlike vasopressin, causes a dose‐dependent degree of pulmonary vasoconstriction . Norepinephrine has primarily alpha 1 receptor activity and produces vasoconstriction with a mild inotropic effect.…”
Section: Medical Treatment Of Hypotensionmentioning
confidence: 99%